Modified Axial Pullout Resistance Factors of Geostrip and Metal Strip Reinforcements in Sand Considering Transverse Pull Effects - Karnamprabhakara, Bhargav Kumar; Chennarapu, Hariprasad; Balunaini, Umashankar (Geotechnical and geological engineering, 2023)
The pullout resistance of reinforcement is an important parameter in the design of reinforced retaining structures. At incipient failure, the kinematics of failure in a reinforced retaining structure shows that the sliding mass of soil pulls the reinforcement obliquely along the slip surface. The response of reinforcement to oblique pull can be considered to be made up of equivalent axial and transverse components of the oblique pull. Accordingly, axial and transverse pullout tests were conducted on geostrip, and metal strip (both smooth and ribbed) reinforcements embedded in uniform sand. Ribbed metal strip reinforcement registered higher pullout resistance than smooth metal strip and geostrip reinforcements. The modified axial pullout resistance factors accounting for transverse pull ranged from 0.44 to 1.23, 1.4 to 3.5, and 2.0 to 5.2 for geostrip, smooth-metal-strip, and ribbed-metal-strip reinforcements, respectively. While the axial pullout resistance factors ranged from 0.34 to 0.65, 0.75 to 1.1, and 0.94 to 1.3.